การคำนวณหาประจุไฟฟ้าที่เป็นฟังก์ชันของเวลาในวงจร RLC ภายใต้แรงดันที่เป็นฟังก์ชันของCosine: การคำนวณหาปรจุไฟฟ้าที่เป็นฟังก์ชันของเวลาในวงจร RLC ภายใต้แรงดันที่เป็นฟังก์ชันของSine - Hutem, Artit; Masoongnoen, Nutnicha; Suwanwong, Sanit; Ellis, Treenuch (วารสารวิทยาศาสตร์และเทคโนโลยี มหาวิทยาลัยราชภัฏบุรีรัมย์ (ออนไลน์), 2021)
In this work, we developed a model of mathematics and physics for the series of the RLC circuit loop. The purpose of this study is to evaluate for finding the time-dependent electric charge that is a consequence of time-dependent voltage force. Which the voltage force is in the cosine function. We calculated by using the second-order non-homogeneous ordinary differential equation and integration by part technique. Wecan find that the time-dependent electric charge corresponds to capacitance but is inversely proportional to induction. The time-dependent electric charge is in contrast to the charge. If and have slightly differentvalues the time-dependentelectric charge behaves like an oscillation wave group.